Promoting Culturally Relevant Educational Practices: Leveraging Locally Designed Instructional Artifacts as Change Agents. Issue 5 (September 2019) - Salisbury, Jason
This qualitative multiple case study assesses two locally designed instructional artifacts created to support teacher enactment of culturally relevant educational (CRE) practices. Attention is paid to artifact's ability to support collective teacher use of CRE and the ways that artifacts acted as proxies for instructional leadership. Findings demonstrate that for artifacts to be successful tools in leading building-wide instructional change, they need to nurture teacher collaboration on supporting youth of color and position professional practice as needing to change. Finally, I analyze the differences between the two instructional artifacts to demonstrate how one was more successful at shifting collective practice.